A study of knuckling effect of soccer ball - Asai, T.; Seo, K.; Sakurai, Y.; Ito, S.; Koike, S.; Murakami, M. (The Engineering of sport 7, Volume 1, 2008)
The aerodynamic properties and boundary-layer dynamics of a non-spinning or slowly-spinning soccer ball are not well understood. The purpose of this study is to discuss the magnitude and the frequency of the side force of non-spinning or slowly-spinning flight soccer ball, which called "knuckling effect ball", using a high speed VTR image of a real place kick. The direct liner transformation method was used to obtain three dimensional coordinates of ball position. The magnitude and the frequency of the side force were measured by a digitizing Software System in PC. The magnitude of the side force in real flight was measured to range from about 1 N to 8 N. Additionally, the frequency of the side force in real flight was estimated to range from 1.0 Hz to 3 Hz.